Erythrocyte membrane anionic content and urinary glycosaminoglycan excretion in type 1 diabetes: Association with retinopathy - (:unkn) unknown (TAYLOR & FRANCIS INC, 2006)
Background: In diabetic nephropathy, increased excretion of glycosaminoglycans and loss of basement membrane anionic charge had been documented to be related with diabetic microalbumuniria. There was no study that studied those two factors in clinical settings with a degree of diabetic retinopathy in type 1 diabetics. Method: Forty subjects ( aged 27.3 +/- 6.3) with type 1 diabetes with different levels of diabetic retinopathy and 30 healthy subjects ( aged 29.52 +/- 8.7) were included in the study. Subjects were first divided as patients without (R-0) and with (R-1) retinopathy. They then were further divided into two subgroups with the help of fundus angiography as diabetic lesions demonstrable with fluorescein angiography (R-1A) and early diabetic retinopathy lesions on fundus examination (R-1B). Erythrocyte anionic charge (EAC) was determined by the binding of cationic dye, alcian blue, and urinary glycosaminoglycan excretion and (U-GAG) was determined spectrophotometrically. Results: UGAG was increased (35.74 +/- 14.01 vs 21.25 +/- 6.19 mu g/mL, 95% confidence intervals [CI], 9.01 - 19.96, p = 0.02) and EAC (62.14 +/- 27.17 vs. 158.53 +/- 36.98 ng alcian blue 10(6) per 10(6) RBC, 95% [CI] - 111.68 - 81.10, p = 0.0001) was decreased significantly in diabetic patients with respect to controls. As the grade of diabetic retinopathy increased, UGAG increased and EAC decreased within subgroups of diabetic patients ( p < 0.005). U-GAG pozitively correlated (r = 0.36 and p = 0.03) and EAC negatively ( r = - 0.695, p = 0.0001) correlated with diabetes duration. EAC and UGAG negatively correlated ( r = - 0.58 and p = 0.0001) with each other in type 1 diabetics. EAC ( p = 0.007) and diabetes duration ( p = 0.001) were found to be the two significant factors to have diabetic retinopathy in diabetics with logistic regression analysis. Conclusion: Although we need more prospective and larger studies to get a direct conclusion, we found that type 1 diabetic patients with less EAC and more UGAG are more likely to have diabetic retinopathy.
Keywords: erythrocyte anionic charge; urinary glycosominoglycan; diabetic retinopathy; GLOMERULAR-BASEMENT-MEMBRANE; EXTRACELLULAR-MATRIX COMPONENTS; DANAPAROID SODIUM; BRUCHS MEMBRANE; HEPARAN-SULFATE; PROTEINURIA; NEPHROPATHY; RAT; CAPTOPRIL; MELLITUS